PROCEDURE FOR RESOLVING CONSUMER DISPUTES THROUGH CONSUMER DISPUTE SETTLEMENT AGENCY (BPSK) - Maryanto Maryanto; Lathifah Hanim; Dini Amalia Fitri (LAW FACULTY UNISSULA, 2021)
The establishment of the Consumer Dispute Settlement Agency (here and after, we will use the acronym BPSK) is to protect consumers and entrepreneurs by designing a Consumer Protection system that contains legal certainty and transparency. The purpose of this study was to determine the procedure for resolving consumer disputes through BPSK. This research uses doctrinal and non-doctrinal approaches. The result of the research is that the procedure for resolving consumer disputes carried out by BPSK is through 2 (two) processes or paths that must be passed if consumers want to resolve consumer disputes with business actors, namely: Dispute Resolution outside the court, namely the process of making a complaint or claim for losses carried out by business actors to BPSK or Non-Governmental Consumer Protection Agency (LPKSM). From these complaints, BPSK is obliged to issue a decision no later than 21 (twenty-one) working days after the claim is received and Dispute Settlement Through the court, namely the process Consumers who feel aggrieved report to the authorities, namely to the police for follow-up as in the dispute resolution process in court. There are 3 (three) ways to settle consumer disputes, namely conciliation, arbitration, and mediation.